Neoplastic transformation and tumorigenesis by the human protooncogene MYC. - Ramsay, G M (1990)
Damage to the protooncogene MYC has been implicated in the genesis of diverse human tumors, but the tumorigenic potential of the isolated gene has been disputed. Here we report the use of a retroviral vector to test the potency of human MYC for neoplastic transformation in avian cells. We found that sustained and abundant expression of MYC can transform both embryonic fibroblasts and hematopoietic cells and elicit granulocytic leukemias in chickens. Transformation by MYC is accompanied by changes in diverse aspects of cellular phenotype, including morphology, ability to grow in suspension, rate of proliferation, the structure of the cytoskeleton, and the composition of the extracellular matrix. Nevertheless, the biological potency of MYC is inherently constrained when compared to that of the retroviral oncogene v-myc. Our findings enlarge on previous descriptions of neoplastic transformation by MYC and sustain the view that ungoverned expression of the gene can contribute to the genesis of human tumors.